Lanthanide-doped zinc gallium oxide (ZnGa2O4) nanocrystals and their engineered photoluminescence - Kim, Kihyo; Kim, Kicheol; Kwon, Hyo Geun; Kim, Sunghoon; Kim, Sang Wook (Macromolecular Research, 2025)
Zinc gallate (ZnGa2O4) has been introduced in various studies as a good host phosphorescent material, and the change of its optical properties by ion doping has received much attention. However, ZnGa2O4 is mostly synthesized through solid-state reactions, the reaction conditions of high temperature and pressure were required, and its low dispersibility often limited its applications. In this study, we synthesized normal spinel structured ZnGa2O4 nanocrystals through a colloidal method. Lanthanide doping specifically with europium and terbium resulted in red (614 nm, photoluminescence quantum yield (PLQY): 2.2%) and green (545 nm, PLQY: 13.6%) emissions under 254 nm UV excitation. By applying the novel co-doping system of europium and terbium to the synthesis of colloidal ZnGa2O4 for the first time, we were able to achieve various color conversions including green, red, and white by adjusting amount and ratio of lanthanide ions. Graphic Abstract: PL emission spectra by adjusting the ratios of Eu3+ and Tb3+ doping and the CIE 1931 chromatography diagram of Eu3+ and Tb3+ co-doping system of ZnGa2O4 nanocrystals (Figure presented.)
Keywords: Co-doping; Colloidal synthesis; Doping system; Gallium oxides; Optical-; Phosphorescent material; Photoluminescence quantum yields; Property; Synthesised; Zinc gallate; Co-doping; Colloidal synthesis; Lanthanide; ZnGa2O4